The Determinants of Student Achievement in Government and Private Schools in Pakistan (The Pakistan Development Review, 2003)
This study is driven by some fundamental issues evolving in Pakistan’s educational set-up. In the past few decades, the country has been experiencing what can only be termed a dramatic revolution in education provision. There has been an explosion of private schooling mostly at the primary but at higher levels as well and, somewhat surprisingly, private schooling cannot be relegated the status of an urban èlite phenomenon alone [Andrabi, et al. (2002)]. This has taken the form of many poor households and those in rural areas opting to send their children to fee-paying private schools rather than the non-fee charging government schools. This transformation of the education sector has generated many concerns among which the ‘equity’ issue has been raised to the fore. The unprecedented growth of cheap private schooling has also raised questions regarding the role of these institutions in the delivery of education, the question of parental ‘choice’1 as well as the future of government educational policy.